2011 International Conference on Reconfigurable Computing and FPGAs 2011
DOI: 10.1109/reconfig.2011.11
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Efficient FPGA Accelerator for Monte Carlo Option Pricing with the Heston Model

Abstract: Today, pricing of derivates (particularly options) in financial institutions is a challenge. Besides the increasing complexity of the products, obtaining fair prices requires more realistic (and therefore complex) models of the underlying asset behavior. Not only due to the increasing costs, energy efficient and accurate pricing of these models becomes more and more important. In this paper we present -to the best of our knowledge -the first FPGA based accelerator for option pricing with the state-of-the-art H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 14 publications
(23 reference statements)
0
23
0
Order By: Relevance
“…Multilevel Monte Carlo has shown promising results with FPGA accelerated designs [7]. Combining multilevel optimisations with mixed precision improvements has also shown strong results [2].…”
Section: Related Workmentioning
confidence: 99%
“…Multilevel Monte Carlo has shown promising results with FPGA accelerated designs [7]. Combining multilevel optimisations with mixed precision improvements has also shown strong results [2].…”
Section: Related Workmentioning
confidence: 99%
“…De Shryver et al [18] found a Xilinx Virtex-5 FPGA accelerated system to be slower, but 2.5 times more energy efficient, than a Tesla C2050 GPU accelerated system for a one dimensional Heston (stochastic volatility) option pricing model. The authors predict that 3 such FPGAs would give similar speeds to the GPU while consuming only 3% of the energy, if the full calculation were performed on the FPGAs.…”
Section: A Previous Work On Acceleration Of Pricing Enginesmentioning
confidence: 99%
“…Still, the energy cost of acceleration is starting to be taken into account as a key performance criterion, along computing times and accuracy. Following this trend, de Schryver, et al [4] have presented a benchmark to compare option pricing accelerators between each other, and not only between an accelerator and a reference software. They define an option pricing accelerator as:…”
Section: Related Workmentioning
confidence: 99%